Methane emission by plant communities in an alpine meadow on the Qinghai-Tibetan Plateau: a new experimental study of alpine meadows and oat pasture - Wang, Shiping; Yang, Xiaoxia; Lin, Xingwu; Hu, Yigang; Luo, Caiyun; Xu, Guangping; Zhang, Zhenhua; Su, Ailing; Chang, Xiaofen; Chao, Zengguo; Duan, Jichuang (Biology letters (2005), 2009)
Recently, plant-derived methane (CH4) emission has been questioned because limited evidence of the chemical mechanism has been identified to account for the process. We conducted an experiment with four treatments (i.e. winter-grazed, natural alpine meadow; naturally restored alpine meadow eight years after cultivation; oat pasture and bare soil without roots) during the growing seasons of 2007 and 2008 to examine the question of CH4 emission by plant communities in the alpine meadow. Each treatment consumed CH4 in closed, opaque chambers in the field, but two types of alpine meadow vegetation reduced CH4 consumption compared with bare soil, whereas oat pasture increased consumption. This result could imply that meadow vegetation produces CH4. However, measurements of soil temperature and water content showed significant differences between vegetated and bare soil and appeared to explain differences in CH4 production between treatments. Our study strongly suggests that the apparent CH4 production by vegetation, when compared with bare soil in some previous studies, might represent differences in soil temperature and water-filled pore space and not the true vegetation sources of CH4.